A novel wideband pattern reconfigurable antenna using switchable parasitic stubs. Issue 4 (28th December 2018) - Jose, Melvin C.; Chithra Devi, R.; Sreeja, B. S.; Meraline, S.; Radha, S.
Abstract: A novel printed wideband pattern reconfigurable antenna using electronically switchable parasitic stubs is presented in this communication. The proposed antenna is compact, made of a low‐cost FR‐4 substrate and operates from 1.88 to 2.55 GHz with −10 dB impedance bandwidth. This antenna used only two PIN diodes and a simple bias control circuit without any vias or dc lines. It has the feature of improved gain, efficiency and two opposite directional patterns radiated in positive or negative x‐axis in the azimuth plane. It has the group delay variations within 2 ns for the wideband operation. The proposed antenna was fabricated and validated for its pattern diversity performance.